Rabdomyosarcoma of the biliary tree - Balkan, Emin; Kırıştıoğlu, İrfan and Gürpınar, Arif and Sınmaz, Kutluğ and Özkan, Tanju and Doğruyol, Hasan (The Turkish Journal of Pediatrics, 1999)
Rabdomyosarcoma of the biliary tree is one of the rare causes of biliary tract obstruction in childhood. Nevertheless it is the most common cause of obstructive jaundice due to neoplastic biliary obstruction. We present a two-year-old child with obstructive jaundice secondary to an embryonal rhabdomyosarcoma of the biliary tree. She underwent surgery and, after total excision of the mass, a hepaticojejunostomy and Roux-en-Y anastomosis were performed. She was referred to the Pediatric Oncology Group for follow-up. Rhabdomyosarcoma of the biliary tree, although rare, must be considered in the etiology of obstructive jaundice in children.